Encouraging English Speaking through Targeted Motivational Strategies: An Action Research - Rai, Pradeep; Nepal, Keshar (Rupantaran: A Multidisciplinary Journal, 2026)
Motivation plays very important role in learning the language. This collaborative action research uses motivational strategies to help create an English-speaking atmosphere in English classrooms. English language teachers are often found using force to create such an atmosphere in their classrooms. This research aims at analyzing the teacher led strategies and investigating motivational strategies to encourage students to speak English. Imposing the rule of ‘English-only’ and punishing students for speaking in languages other than English (in this case, Nepali) can have negative repercussions: students may speak even less, or may not speak at all due to fear or hesitation. The same situation was identified in an English-medium private school through Focus Group Discussions (FGDs) with English teachers and students separately. Suggested by the FGDs and informed by the review of relevant literature, some motivational strategies were formulated and implemented as an intervention. A month-long classroom observation showed that if students are properly motivated, they will speak in English freely and voluntarily, without the need for enforcement. However, a few limitations to the effectiveness of the motivational strategies were also identified, such as the short-lived nature of motivation, insufficient class time for interaction, and students’ preference for intrinsic over extrinsic motivation. The study concludes that well-planned motivational strategies can contribute to creating a better and healthier English-speaking atmosphere in the classroom.